PENGARUH SIKAP KERJA, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN LABUHANBATU SELATAN - Sahrul Tarigan; Rasman .; Oryza Kuspranataga; T. Muhammad Iqbal; Puti Andam Sari (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
Problem of this study how influence of job attitude on performance. How influence of job environment on performance. How influence of job motivation on performance. How influence job attitude, job environment and job motivation on performance. The purpose of this study to determine and analyze the effect of job attitude on performance. Determine and analyze the effect of job environment on performance. Determine and analyze the effect of job motivation on performance. Determine and analyze the effect of job attitude, job environment and job motivation on performance. Sample in the study is 52 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job attitude variable has a positive and significant effect on performance. Job environment variable has a positive and significant effect on performance. Job motivation variable has a positive and significant effect on performance. Job attitude, job environment and job motivation variable has a positive and significant effect on performance.